Leaching of indium and tin from waste LCD by a time-efficient method assisted planetary high energy ball milling. (1st February 2021) - Qin, Jianchun; Ning, Shunyan; Fujita, Toyohisa; Wei, Yuezhou; Zhang, Shichang; Lu, Siming
Graphical abstract: Highlights: A process combined grinding and acid leaching was proposed to dispose waste LCDs. This process maximally recovered valuable resources within an efficient time. The particles with size less than 0.035 mm were agglomerated each other. Addition of H2 O2 decreased leaching rate for the particle size less than 0.075 mm. Recovery of In and Sn were obtained with 96.9% and 85.6% for 90 min of leaching. Abstract: The phenomenon of the long leaching time and low leaching rate is presented in the acid leaching process under the conventional conditions of low reaction temperature and acid concentration. In order to promote leaching rates of indium and tin in waste liquid crystal display, an optimized process combining rapid milling and acid leaching has been proposed, which is more time and energy-efficient, environmentally sound compared with the traditional acid leaching process. Leaching mechanism analysis was conducted to uncover the different leaching behavior of indium and tin. And the external factors affecting the leaching rates of indium and tin were studied to optimize. In this process, the fine powder with a weight ratio of 97.6%, which particle size less than 0.075 mm, was obtained with the optimal milling time of 30 min by rapid grinding in the planetary high energy ball milling. About −0.003 l/s of grinding rate constant was performed in the grinding size fraction from 3 mm to 0.075 mm. The research results indicated that the particle size less than 0.035 mm was agglomerated, and the addition of H2 O2 reduced the leaching rate for the particle size less than 0.075 mm. Moreover, 86.3% and 76.1% of indium and tin were leached in a short leaching time of 10 min by using 3 M H2 SO4 at 85 °C for particle size range from 0.075 to 0.035 mm, while 96.9% and 85.6%, respectively in 90 min.